The Unconstitutionality of Termination of Employment on The Grounds of An Urgent Offence - Mohamad Fandrian Adhistianto (Universitas Negeri Semarang, 2023)
Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation through Government Regulation No. 35 of 2021 on Fixed-term Labor Contracts, Outsourcing, Breaks during working time and Dismissal provides for dismissal for urgent infractions that are similar in content to dismissal for serious infractions. misconduct under the Manpower Act No. 13 2003, which was repealed based on a decision of the Constitutional Court No. 012/PUU-I/2003. The legal issues that will be addressed in this study are how the constitution envisages dismissal for urgent violations, which are similar in substance to serious misconduct as grounds for dismissal. This type of research is legal research using statutory approach and is carried out by searching for positive legal norms consisting of applicable laws and court decision related to termination of employment on the grounds of urgent violations apply based on Law Number 6 of 2023, although it has similar substance with gross misconduct as a reason for termination of employment in the provisions of Article 158 of Law Number 13 of 2003 which has been declared contrary to the 1945 Constitution so that it does not apply and has binding legal force based on the Constitutional Court Decision Number 012/PUU-I/2003.